Damage assessment of single-layer reticulated domes subjected to mainshock-aftershock sequences based on structural damage factor. (December 2021) - Huang, He; Wang, Yifan; Li, Yugang
Abstract: Long-span infrastructures are usually taken over for public shelters, in which single-layer reticulated dome is a kind of popular structure. But there was less research for the damage assessment of single-layer reticulated domes subjected to mainshock-aftershock sequences. How to accurately assess the damage by mainshock and the stability redundancy for aftershock becomes an important problem. In order to explore the effects on the structural damage, this paper processes the dynamic time-history analyses for single-layer reticulated domes subjected to mainshock-aftershock sequences. The finite element model of Kiewitt8 single-layer spherical reticulated shell structure is established in ANSYS. Ten pairs of ground motion sequences in horizontal direction are generated with modulating amplitude to simulate the rare and extreme earthquakes. The results demonstrated that the structure even suffered from the extreme earthquake mainshock still has loading capacity and structural safety with the local plastic damage. But the effect on structural damage of aftershock ground motion with greater earthquake intensity cannot be ignored for single-layer reticulated domes. A structural damage assessment method is utilized with combining the damage factor by performing static stability analysis twice. It can effectively reflect the remaining loading capacity and structural safety factor for the practical seismic engineering applications.